PERBEDAAN PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIK SISWA SMK MELALUI PENDEKATAN CONTEXTUAL TEACHING AND LEARNING DAN PEMBELAJARAN KONVENSIONAL - Setiawati, Diah (LPPM Institut Pendidikan Nusantara Global, 2023)
This study aimed to determine: (1) The difference upgrades between the mathematical communication skills that students acquire learning through approach Contextual Teaching and learning and students receiving learning through conventional learning, (2) The interaction between learning approaches and early math skills of students (high, medium and low) to increase students' mathematical communication skills. This study is a semi-experimental study. The study population was a class X student of SMK Negeri 1 Bireuen, with two lines ANOVA analysis and t-test. The results showed that (1) There are differences in students' mathematical communication skills improvement among students who received learning approach CTL to increase students' mathematical communication skills, (2) There is no interaction between teaching approaches used and early math abilities of students to increase mathematical communication skills students. Based on the results and discussion of the research that has been described, it can be concluded that there are differences in improving students' mathematical communication skills between students who get the contextual teaching and learning/CTL learning approach and improving students' mathematical communication skills who get conventional learning.